Perceived stress, social support and coping strategies on retired teachers' psychological well-being. - Barcelona, Mary Racelyn T.
Retirement poses significant changes in the lives of the old age population. Along with this are changes in social networks, activities and life outcomes. To examine perceived stress, social support, coping strategies and psychological well-being among retired teachers in Tigbauan, Iloilo, qualitative and quantitative measures were conducted to 41 retired teachers. In general, retired teachers perceive low levels of stress. Factors that contribute to perceived stress are health conditions, financial concerns, family problems and current activities. Social support, which is provided primarily by family and friends, is experienced in high levels. In terms of coping, emotion-focused coping is engaged in by majority. The leading specific coping strategy they employ is praying or going to church. The majority experience positive levels of psychological well-being, which can be predicted using the variable of social support, as revealed by regression analysis